Cancellation of Grants Transferred In The Form Of Inheritance Through The Supreme Court Decision - Sebayang, Muhammad Alfalah; Harahap, Mhd. Yadi (Cattleya Darmaya Fortuna, 2024)
Research activities must have clear objectives to achieve. Research objectives show the quality and value of research. The objectives to be achieved in this research are to analyze the judge's considerations in deciding the grant cancellation case and to explain the judge's considerations in canceling the first decision after it was ratified AS well AS regarding the authority of the Court in adjudicating disputes over the withdrawal of grants transferred in the form of inheritance. This research has positive legal implications for efforts to realize the rights that should be given to grantees and families of grantees who have been transferred in the form of inheritance. This qualitative research was conducted by collecting, analyzing and interpreting narratives into visual data to obtain a complete, comprehensive and holistic understanding of the phenomenon of adjudicating grant disputes. The results of this study reveal that the urgency of studying Islamic fiqh and the two sets of KHI article 212 and KHES articles 719 and 728 are to become more familiar in resolving sharia economic disputes such as AS the withdrawal of grant assets. And so that both can be used AS guidelines, not just one of them, so that they can be collaborated and do not conflict with fiqh rules. The results of this study are expected to contribute ideas for the development of legal science in Indonesia and especially civil law, especially regarding cases of settlement of grant withdrawals in court.